Environment disaster linkages - Shaw, Rajib; Tran, Phong (Bingley, U.K. : Emerald, 2012)
Disaster management has historically focused on reactive approaches, but a shift to proactive approaches is crucial for addressing concerns raised by the changing environment. A prime reason for the absence of proactive approaches in disaster/hazard management is the uncertainty or ambiguity present in the links between the environment and the hazards. This is the first book to focus on explicit linkages between the changing environment and disasters and suggests better approaches towards disaster management. A ready-reference for field practitioners it combines academic research and field practices and covers areas such as: elements of environmental entry (water-related disasters, desertification and land degradation, typhoon risk management, catastrophic flood and forest management, and coastal issues); impacts of environment and disaster (livelihoods impacts, human health: post-disaster waste management); and strategies, planning and the way forward (climate change adaptation as a planning tool, urban planning and land use planning, mangrove management as a coastal planning tool, and environment disaster education and risk communication).
ch. 1. Environment disaster linkages : an overview / Phong Tran and Rajib Shaw -- ch. 2. Water : water, communities and disasters : inter-linkages / Rajib Shaw -- ch. 3. Air : typhoon and tornado risk management / Yukio Tamura ... [et al.] -- ch. 4. Land : proactive management of drought and its derived disasters in Mongolia / Masato Shinoda -- ch. 5. Forest : catastrophic flood and forest management in Vietnam / Phong Tran and Rajib Shaw -- ch. 6. Coast : coast and communities : the linkages / Rajib Shaw and Ramaswamy Krishnamurthy -- ch. 7. Urban : urban climate resilience as a planning tool in Vietnam / Phong Tran and Rajib Shaw -- ch. 8. Livelihoods : linking livelihoods and ecosystems for enhanced disaster management / Noralene Uy, Rajib Shaw and Yukiko Takeuchi -- ch. 9. Employment : interrelationship of disaster and employment from the perspective of urban-rural linkages in India / Nitin Srivastava and Rajib Shaw -- ch. 10. Health : impacts of salinity, arsenic and drought in south-western Bangladesh / M. A. Abedin, Umma Habiba and Rajib Shaw -- ch. 11. Waste : disaster waste management : an overview / Muralee Thummarukudy -- ch. 12. Land use : urban and land use planning for disaster resilience / Jonas Joerin and Rajib Shaw -- ch. 13. Ecosystem : values of the mangrove ecosystem of Gujarat, India and its socio-economic implications / R. Parthasarathy and Soumini Raja -- ch. 14. Eco-villages : can eco-villages be a build back better strategy after tsunami disasters? / Miwa Abe, Rajib Shaw and Yukiko Takeuchi -- ch. 15. Education : climate change issues in education sectors : an environmental entry point of risk reduction / Rajib Shaw and Phong Tran -- ch. 16. Technology : information and communication technologies (ICT), water and climate change : Asian priorities / Rajib Shaw -- ch. 17. Way forward : environment disaster linkages : a way forward / Rajib Shaw, Phong Tran.
Includes index.
Print version record
Keywords: Nature -- Environmental Conservation & Protection; Nature -- Natural Disasters; Nature -- General; The environment; Natural disasters; Environmental disasters -- Forecasting; Environmental disasters -- Prevention; Emergency management